Seeing is believing? approaches to visual research - Pole, Christopher J. (Christopher John), 1959- (Amsterdam ; Oxford : Elsevier JAI, 2004)
Recent years have seen an increase in the use of visual methods of research across the social sciences. As researchers realize the potential of the visual, not only as a source but also as a means of generating data, a range of techniques has been developed which seek data that are different from those offered by more conventional qualitative research methods. The contributions to this collection start from the premise either that visual research allows a view of the social world which is not available by other means, or that its use offers a means of augmenting other methods, such as discussion and interview. Rather than providing a step-by-step guide to the use of visual methods, the various authors draw on their experience of visual research to provide critical and reflexive accounts of its use in the field, its potential for unlocking otherwise unseen places, spaces and social action and as a basis for the generation of conceptual and theoretical insight.
Visual research: potential and overview / Christopher J. Pole -- History through the lens: every picture tells a story / John Martin and Ruth Martin -- Snap happy: toward a sociology of "everyday" photography / Barbara Harrison -- Recording the "habitus" / Tim Dant -- Performance, self-representation and narrative: interviewing with video / Sarah Pink -- On using visual data across the research process: sights and insights from a social geography of people's independent learning in times of educational change / Pat Allatt and Caroline Dixon -- Images, interviews and interpretations: making connections in visual research / Alan Felstead, Nick Jewson, and Sally Walters -- Power, inequality, change and uncertainty: viewing the world through the development prism / Matt Smith and John Donnelly -- Using visuals to release pupils' voices: emotional pathways into enhancing thinking and reflecting on learning / Andrea Raggl and Michael Schratz -- The use of the visual medium for program evaluation / Rosalind Hurworth.
Includes bibliographical references.
Description based on print version record.
Keywords: Social sciences -- Research -- Methodology; Social sciences -- Research -- Audio-visual aids; Visual sociology; Qualitative research; Social research & statistics; Social Science -- Research